Diffuse Reflectance Spectrophotometers Based on C12880MA and C11708MA Mini-Spectrometers Hamamatsu - V. A. Firago; N. V. Levkovich; K. I. Shuliko (Приборы и методы измерений, 2022)
Diffuse reflection spectroscopy with spatial resolution is a promising direction of non-destructive control of the properties of a number of scattering fine-dispersed materials, including food products. It can find wide practical application only in the presence of compact, easy-to-use and inexpensive spectrophotometric equipment. The aim of the article is to investigate the possibility of creating portable spectrophotometers based on Hamamatsu mini-spectrometers, which work together with modern computing facilities.The schematics for connecting the C12880MA and C11708MA mini-spectrometers to portable computing devices are reviewed. Shows the feasibility of using a small-sized microprocessor board ARM STM32F103C8T6 (Blue pill) on the chip STM32F103C8T6. Its use in the connection scheme has simplified data exchange with the control computer via USB interface and the formation of all the signals that are needed to control the mini-spectrometer.Two experimental samples of spectrophotometers based on C12880MA and C11708MA mini-spectrometers and STM32 microprocessors were created and their characteristics were studied. The calibration procedure and features of the software for these spectrophotometers are presented. The described features ensure the efficiency of software modification for the spectrophotometric problem to be solved. The presence of distortions of the registered spectra in the short-wave part of the spectral range of C12880MA was revealed. They arise due to focusing by the concave diffraction grating of a part of the radiation scattered by it into zero order.Approbation of developed portable spectrophotometers based on Hamamatsu mini-spectrometers indicates the possibility of their use in portable spectrophotometric equipment and devices for spectral control of optical properties of scattering materials. The described calibration technique allows you to determine the range of the spectrum, in which the distortions of the recorded spectra are minimal. The proposed solutions significantly reduce the cost of diffuse reflectance spectroscopy devices with spatial resolution and expand the possibilities of their use in various branches of science and industry.